FEATURES OF THE BUDGETING PROCESS - Gulmira Nurzhanova (Research Retrieval and Academic Letters, 2025)
Budgeting is a key management tool for modern companies building an effective planning system. The stability and development of an organization largely depend on how competently the budget formation process is organized and what principles underlie it. Plans may vary in detail, duration, and level of ambition, but their mandatory characteristics are realism, consistency, and alignment with the overall strategy of the enterprise. Regardless of the scale of the business, its field of activity, or market position, a well-developed plan helps unite employees around common goals. The effectiveness of a company’s work is determined by how harmoniously the plans of individual structural units are linked together. The personality of the manager also plays a significant role: their professionalism, exactingness, and authority have a significant impact on the successful implementation of the budgeting system. At the same time, poorly drafted plans inevitably lead to negative consequences. Underestimated indicators, excessively long deadlines, or unreasonable targets undermine employee motivation, reduce trust in the management system, and raise doubts about the team’s ability to achieve its goals. The planning process must ensure that the company’s strategic objectives are achieved within the set deadlines, and the manager must coordinate the actions of all participants, applying a systematic approach based on knowledge, experience, and the ability to translate strategic guidelines into clear and motivating actions for the team